Ovariální hyperstimulacní syndrom s perikardiálním a pleurálním výpotkem komplikovaný supraventrikulární arytmií - Sovová, E; Oborná, I; Dostál, J; Marek, D; Lukl, J; Talas, M (Casopis lekaru ceskych, 1999)
Problems which arise in conjunction with the use of assisted reproduction methods are no longer resolved only by the gynaecologist. The authors demonstrate on the case of a female patient the necessity of interdisciplinary collaboration in the diagnosis and therapy of developed ovarian hyperstimulation syndrome (OHSS)--the most serious complication of assisted reproduction.
Keywords: Ovarian Hyperstimulation Syndrome; perikardiální efuze; pleurální výpotek; Adult; Pleural Effusion; lidé; dospělí; Female; ženské pohlaví; supraventrikulární tachykardie; Pericardial Effusion; Tachycardia, Supraventricular; ovariální hyperstimulační syndrom; Humans